2013
DOI: 10.1166/jbn.2013.1555
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymeric Nanocapsules Based on Poly(DL-lactide) for Genistein Topical Delivery: Obtention, Characterization and Skin Permeation Studies

Abstract: The isoflavone genistein (GEN) is a natural product with potential applications for skin cancer treatment and chemoprevention; however its high lipophilicity and chemical instability limits its clinical use. Therefore, attempts towards protecting GEN against degradation and increasing its penetration in the skin might be a valid approach. In this work, GEN loaded-PLA nanocapsules (GEN-NC) were prepared by interfacial deposition of preformed polymer (nanoprecipitation); physicochemical characterization and stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In vivo studies showed that Lyso-7 has high potency within this class of drugs (3 mg/kg) compared to other anti-inflammatory drugs, indomethacin (10 mg/kg), and TZDs, pioglitazone (50 mg/kg) [10,11], which enables the use of such Lyso-7-NC formulation even though the drug payload was not very high (7% wt/wt). However, lower payloads of 0.6-1.4% and 1.3-3% wt/wt were recently reported for genistein PLA NC [28] and hydrophobic phtalocyanine in PLA NC, respectively [17]. Furthermore, similar payload of 4-6% wt/wt was obtained with docetaxel in PLGA NC [29].…”
Section: Discussionmentioning
confidence: 80%
“…In vivo studies showed that Lyso-7 has high potency within this class of drugs (3 mg/kg) compared to other anti-inflammatory drugs, indomethacin (10 mg/kg), and TZDs, pioglitazone (50 mg/kg) [10,11], which enables the use of such Lyso-7-NC formulation even though the drug payload was not very high (7% wt/wt). However, lower payloads of 0.6-1.4% and 1.3-3% wt/wt were recently reported for genistein PLA NC [28] and hydrophobic phtalocyanine in PLA NC, respectively [17]. Furthermore, similar payload of 4-6% wt/wt was obtained with docetaxel in PLGA NC [29].…”
Section: Discussionmentioning
confidence: 80%
“…Genistein has been extensively studied in different types of cancers cells and cancer animal models [104]. Unfortunately, the low oral bioavailability of genistein [105], due to its high lipophilicity and its extensive metabolism by the phase II enzymes [106], has limited its use in clinical trials [107].…”
Section: Isoflavonoids: New Insights Regarding Cancer Chemopreventionmentioning
confidence: 99%
“…De Zampieri et al [112] found that GEN-nanoparticles resulted in a higher amount of GEN accumulation in deeper layers of the skin and GEN-nanoparticles might be a promising nanocarrier system for skin delivery of GEN and skin cancer prevention and treatment. Other studies have demonstrated that nano-GEN demonstrated a sustained release manner, increased GEN uptake by cancer cells and enhanced anti-cancer activities of GEN in different cancer cells [113, 114] .…”
Section: Phytochemicals-loaded Nanoparticles and Their Anti-cancer Acmentioning
confidence: 99%